Autorzy:Ewa Duvnjak, Ewa Kokiernak-Jurkiewicz
Wydawnictwo:WSiP
Rok wydania:2015
Oblicz wartość wyrażeń 4.22 gwiazdek na podstawie 9 opinii

`a)\ (-0,25)^2:(-1/8):(-2)^2-(-1000)^0=` 

`\ \ \ =(-1/4)^2*(-8/1):((-2)*(-2))-1=` 

`\ \ \ =(-1/4)*(-1/4)*(-8):4-1=` 

`\ \ \ =1/strike16^2*(-strike8^1)*1/4-1=`  

`\ \ \ =-1/2*1/4-1=-1/8-1=-1 1/8` 

 

 

`b)\ [(-0,5)^3+2 1/4]:[(-0,25)+(-2)^2]=` 

`\ \ \ =[(-1/2)^3+2 1/4]:[(-1/4)+(-2)*(-2)]=` 

`\ \ \ =[(-1/2)*(-1/2)*(-1/2)+2 1/4]:[-1/4+4]=`  

`\ \ \ =[-1/8+2 2/8]:3 3/4=2 1/8:3 3/4=` 

`\ \ \ =17/8:15/4=17/strike8^2*strike4^1/15=17/30` 

 

 

`c)\ -(-5)^2*1/5^3-(2,3-2 1/2)^2=` 

`\ \ \ =-(-5)*(-5)*1/(5*5*5)-(2,3-2,5)^2=` 

`\ \ \ =-25*1/125-(-0,2)^2=` 

`\ \ \ =-1/5-(-0,2)*(-0,2)=` 

`\ \ \ =-0,2-0,04=-0,24` 

 

 

`d)\ -4^2-0,4^3:(-0,64)-(1/2)^0=` 

`\ \ \ = -4*4-(0,4*0,4*0,4):(-0,64)-1=`  

`\ \ \ =-16-0,064:(-0,64)-1=`  

`\ \ \ =-16-6,4:(-64)-1=` 

`\ \ \ =-16-(-0,1)-1=-17+0,1=-16,9` 

 

 

`e)\ -2^2-(13-7^2)-(-0,1)^3*10^3=` 

`\ \ \ =-2*2-(13-7*7)-(-0,1)*(-0,1)*(-0,1)*10*10*10=` 

`\ \ \ =-4-(13-49)-(-0,001)*1000=` 

`\ \ \ =-4-(-36)+1=` 

`\ \ \ =-4+36+1=33`